Penerapan Pembelajaran Creative Problem Solving (CPS) Berbasis Scienstific Approach Terhadap Kemampuan Berpikir Kreatif Dan Kreativitas Dalam Memecahkan Masalah - Sugono Sugono; Sofyan Hasanudin Nur; Asep Ginanjar Arip (Edubiologica: Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2018)
The background of this study is that the learning process still uses conventional learning (lecture method) so that there are problems with the ability of creative thinking and student creativity in solving problems. The purpose of this study is to find out the implementation of Scientific Problem Solving (CPS) based Learning to improve the ability to think creatively and Creativity in solving problems.This research method used an experiment with prepostes control group design which was carried out in Kapetak State Middle School SMP2 with 39 students in the experimental class and 38 students in the control class.The results of this study concluded that (1) The implementation of learning using the CPS-based scientific model seemed that the teacher was able to carry out good learning. This is indicated by the implementation of all the CPS-based scientific model syntax indicators by teachers with an average total implementation of the learning process of 87.78% with a very good category. (2) Implementation of the application of scientific-based CPS learning model in teaching and learning activities can improve students' creative thinking skills. This is reflected in the average value of creative thinking achieved by the control class is 65.33, and the average value of creative thinking in the experimental class is 78.89 in the good category. Hypothesis test results are sig. 0.000 <0.05, then the initial hypothesis (H0) is rejected. This means that there are differences in the average creative thinking of students between the experimental class and the control class. (3) There are differences and enhancements in students' creativity in solving problems between those who use the Scientific Creative CPS learning model and those who use learning material lectures on the Excretion System in human students where the experimental class has increased from a pretest value of 55.13 to 75.43, with a value normalized gain 0.43 which is Medium. Whereas in the mean control class from pretest 52.85 it rose to 60.96 in the posttest average, with the normalized gain value of 0.16 which included the low criteria (4) Student responses Regarding creative thinking skills and creativity solving problems after the science learning activities with the CPS learning model Scientific based through questionnaires obtained an average value of 55.18 and categorized as good. This means that the learning model has an influence on the skills of creative thinking and creativity in solving problemsKeywords: Creative thinking; Creativity solving problems; Creative Problem Solving (CPS)